Factors that influence the acceptance of internet of things services by customers of telecommunication companies in Jordan - Al-Momani A.M.; Mahmoud M.A.; Ahmad M.S. (IGI Global, 2023)
Internet of things; Sales; Ubiquitous computing; Web services; Automated services; Behavioral intention; Internet of thing (IOT); IT services; Technology acceptance model; Technology adoption; Telecommunication companies; User satisfaction; Telecommunication services